Effect of deposition temperature on the structural and crystallinity properties of self-catalyzed growth Indium Tin Oxide (ITO) thin film using CVD technique - Mohd Yunus, Mardhiah; Saroni, Azianty (Universiti Teknologi MARA, Perlis, 2025)
Indium Tin Oxide (ITO) is one of the electronic materials that is widely used as a transparent conductor in optoelectronic device applications. The growth techniques of ITO are crucial in order to grow the best structure of ITO for the better performance application. The main objective of this study to investigate the effect of deposition temperature (1000 °C, 1100 °C, and 1200 °C) on their structural and crystallinity properties of self-catalyzed ITO thin film synthesized using chemical vapor deposition (CVD) technique. The ITO thin films were deposited onto silicon substrates using a tube furnace via the CVD technique, utilizing a precursor mixture of indium(III) oxide (In₂O₃) and tin(IV) oxide (SnO₂), with argon gas used as the carrier. Scanning Electron Microscopy (SEM) showed that thin film at 1100 °C exhibited well-defined shapes, minimal aggregation, and an average diameter of 0.46 µm, making it the optimal temperature for synthesizing high-quality ITO thin film. Energy-dispersive X-ray (EDX) analysis confirmed the homogeneous distribution of indium, tin, and oxygen at this temperature, with the highest compositional homogeneity of 56.46%. Moreover, XRD pattern confirms the presence of peak at 2θ = 31.1° corresponds to the (320) plane of cubic indium tin oxide (In2Sn2O7) across all samples. Results show that as the deposition temperature increased,structures with well-defined shapes were formed, and the crystallinity was enhanced. The crystallite size increased from 35.21 nm to 103.05 nm as at 1000 °C and 1200 °C, respectively with a corresponding decrease in lattice strain in the structure. These findings demonstrate how crucial the deposition temperature in determining the ideal structural properties of ITO thin film for application in particular optoelectronic devices.